Reduction of methomyl and acetamiprid residues from tomatoes after various household washing solutions - Rasolonjatovo, M. Angela; Cemek, Mustafa; Cengiz, M. Fatih; Ortac, Deniz; Konuk, H. Buesra; Karaman, Elif; Kocaman, A. Tuba (Taylor & Francis Inc, 2017)
The removal of pesticide residues is essential in order to control and reduce the harmful effects of pesticides commonly used in agriculture. The aim of this study was to investigate the effectiveness of 18 different household washing solutions for the reduction of methomyl and acetamiprid residues from tomatoes. These basic household solutions were used to prepare washing solution to remove pesticides. During this study, tomatoes were divided into two groups: in the first group, tomatoes were treated with the pesticides and the second group was washed with household solutions (distilled water, acetic acid, sodium chloride, ethanol, sodium bicarbonate, hydrogen peroxide, sodium hypochlorite, and liquid soap, lemon juice, mineral water, zam-zam water, whey, milk, and their combinations) after treating with pesticides. The pesticides residues in all samples were extracted by the QuEChERS technique, analyzed by LC-MS/MS. The results showed significant reduction in residues of all washed groups compared with the control (p < 0.01). Acetic acid, sodium chloride+sodium bicarbonate, zam-zam water, acetic acid+sodium chloride, sodium hypochlorite, milk, acetic acid+sodium chloride+sodium bicarbonate, liquid whey, liquid soap, lemon juice, ethanol, and sodium bicarbonate were found to remove more than 50% of both pesticide residues. The effectiveness of washing solutions was different for every type of pesticide. In the same way, blend of washing solutions has shown a synergetic effect on the removal of pesticides and was more effective compared to one solution. This research has raised the potential use of household solutions easily found at home that could be used to remove pesticide residues.
Keywords: Pesticide residue; Methomyl; Acetamiprid; Tomatoes; Washing; Household